(untitled) (Bangladesh Journal of Urology, 2020)
A forty eight year old woman with the clinical diagnosis of renal mass due to renal cell carcinoma was found to have renal tuberculosis. The clinical presentation and management are being discussed. Bangladesh Journal of Urology, Vol. 15, No. 2, July 2012 p.56-58